UPAYA MENINGKATKAN EMPATI KULTURAL PADA SISWA SMA MELALUI BIMBINGAN KELOMPOK TEKNIK ROLE PLAYING - Triana, Dian (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2022)
Humans are social creatures who need the presence of other humans, in carrying out their roles on earth, humans will not be able to achieve what they want without the help of other humans. Role playing techniques introduce various important principles in social life, hone creativity and improve empathy and language skills. The purpose of this study was to increase cultural empathy between peers and help solve the problem of students' lack of empathy for other students of different cultures. The type of research used in this research was classroom action research which was carried out in two cycles. Every cycle consisting of planning , the act of , observation , and reflection .A subject of study consisting of student of class xii amounting to 12 students .This research result indicates that empathy students has increased significantly each siklusnya .So that it can be concluded that guidance role playing the technique can increase its cultural empathy at the different cultural. Keywords: group guidance, role playing method, empathy